Structural changes, expression of dream, BDNF and CREB proteins in the hippocampus; and spatial learning and memory of rapid eye movement (REM) sleep-deprived rats upon acute nicotine treatment - Rashid, Norlinda Abd (2018)
Rapid eye movement sleep deprivation (REMsd) has been shown to disturb spatial learning and memory performance, while acute nicotine treatment prevented these effects. This study was conducted to investigate the mechanisms of REMsd and the use of nicotine in preventing impairments in spatial learning and memory by investigating the expression of ‗downstream regulatory element antagonist modulator’ (DREAM), ‘cyclic AMP response element binding protein’ (CREB), and ‘brain-derived neurotrophic factor’ (BDNF) proteins; and ultracellular changes in the rat‘s hippocampal cells. Ten-week-old male Sprague Dawley rats weighing 200-250 g were divided into six groups. The first (Control (C), n=24) and second to eliminate nicotine effect on control group (Control and nicotine (CN), n=24) groups comprised freelymoving control rats; groups 3 (REMsd (R), n=24) and 4 (REMsd and nicotine (RN), n=24) consisted of rats with REMsd induced using the inverted flower pot technique for 72 hours; and the fifth (Wide platform (W), n=24) and sixth (Wide platform and nicotine (WN), n=24) groups comprised rats which were exposed to the same experimental environment as the REM sleep-deprived rats, however, the inverted flower pot used for this group was wider, hence enabling the rats to sleep. The C, R, and W groups were injected with normal saline subcutaneously while the CN, RN and WN groups were injected with 1 mg/kg nicotine subcutaneously every 12-hourly for 72hours. The Morris Water Maze (MWM) (n=36) instrument was used to determine the spatial learning and memory performances, by which the initial 5 days was for the ‗escape latency’ test and the final day ‗probe’ test. Food consumption and body weight gain were measured for all groups during adaptation, 72 hours induction period, and during MWM period. For each group, hippocampi were removed for immunohistochemistry (IHC) (n=36), Western blotting (WB) (n=36), and transmission electron microscopy (TEM) analysis (n=36) separately. The REMsd in the R and RN groups was confirmed by REMsd-induced hyperphagia and weight loss. In the rats of R group, there was marked spatial and memory impairment; TEM analysis showed damages in the cytoplasm, nuclei, mitochondria, rough endoplasmic reticulum (RER) and golgi apparatus (GA); IHC showed that these rats had higher total number of DREAM-positive neurons, but lower total number of pCREB- and BDNF-positive neurons in the ‗cornu ammonis’ (CA) - CA1, CA2 CA3, and ‗dentate gyrus’ (DG) hippocampal regions; and these results were consistent with those of the WB analysis. Nicotine-treated group RN rats, showed reduction of REMsd effects. In conclusion, this study showed that acute nicotine treatment in REMsd reduced impairments in spatial learning and memory by (1) attenuating the hippocampal ultrastructure damage, (2) reducing the DREAM protein expression and level, and (3) increasing the pCREB and BDNF protein expressions and levels, in the hippocampi of REMsd rats.